Controlled Continuous ∗-K-g-Frames for Hilbert C∗-Modules. (29th April 2021) - Touri, Abdeslam; Labrigui, Hatim; Rossafi, Mohamed; Kabbaj, Samir
Abstract : Frame theory has a great revolution for recent years. This theory has been extended from Hilbert spaces to Hilbert C ∗ -modules. In this paper, we define and study the new concept of controlled continuous ∗ -K -g -frames for Hilbert C ∗ -modules and we establish some properties.